Remdesivir use and antimicrobial stewardship restrictions during the coronavirus disease 2019 (COVID-19) pandemic in the United States: A cross-sectional survey - Alfredo J. Mena Lora; Rodrigo Burgos; Scott Borgetti; Lelia H. Chaisson; Susan C. Bleasdale (Cambridge University Press, 2023)
Deploying therapeutics for coronavirus disease 2019 (COVID-19) has proved challenging due to evolving evidence, supply shortages, and conflicting guideline recommendations. We conducted a survey on remdesivir use and the role of stewardship. Use differs significantly from guidelines. Hospitals with remdesivir restrictions were more guideline concordant. Formulary restrictions can be important for pandemic response.